Implementation of Denpasar Mayor Regulation Number 22 of 2023 concerning Women-Friendly and Child-Friendly Villages in Penatih Dangin Puri Village, East Denpasar District, Denpasar City - Sukma Eka Putri, Ni Wayan Ayu; Astawa, I Wayan; Sulandari, Sri; Ana Muliasari, Wahyu (Indonesian Association for Public Administration (IAPA), 2025)
This study aims to analyze the implementation of Denpasar Mayor Regulation Number 22 of 2023 concerning Women-Friendly and Child-Friendly Villages (DRPPA) in Penatih Dangin Puri Village, East Denpasar District, Denpasar City. This study uses a qualitative descriptive approach with data collection techniques in the form of interviews, observations, and documentation studies. The theory used in analyzing the implementation of this policy is the implementation model of Donald Van Meter and Carl Van Horn, which includes six main indicators, namely policy standards and goals, resources, characteristics of implementing organizations, communication, implementing disposition, and environmental conditions. The results of the study show that the Village Government has carried out various programs such as the establishment of children’s forums, strengthening the role of PKK, posyandu, and collecting data on women and children. However, there are still several obstacles such as the lack of understanding of the substance of the regulations, the lack of optimal socialization to the community, and the lack of the formation of special institutions and village regulations (awig-awig) that support the program. In addition, public participation is also still low due to lack of information and awareness. The conclusion of this study is that the implementation of regulations has not been optimal. It is necessary to increase the capacity of human resources, effective communication, and support for local regulations so that the implementation of DRPPA can be achieved comprehensively and sustainably.